FluxomicsExplorer: Differential visual analysis of Flux Sampling based on Metabolomics. (November 2022) - Holzapfel, Constantin; Hoene, Miriam; Zhao, Xinjie; Hu, Chunxiu; Weigert, Cora; Niess, Andreas; Xu, Guowang; Lehmann, Rainer; Dräger, Andreas; Krone, Michael
Abstract: Flux Sampling (FS) is an unbiased constraint-based modeling method in systems biology that characterizes the admissible metabolic flux space of cells and organisms at a molecular level. It returns information about reaction flux ranges and their probability from a genome-scale metabolic model (GEM), which can be used to predict metabolic phenotypes. FS is particularly beneficial if a cellular objective cannot be easily identified. We present FluxomicsExplorer, a web-based visual analysis application that facilitates a data- and task-driven exploratory analysis of FS results. It was designed together with experts in medicine and systems biology to satisfy their requirements and offers multiple linked views that visualize the standardized scoring of flux differences, flux distributions, and the network of biological pathways to guide the analysis process. Instead of focusing on a subset of known influential reactions for the analysis, it allows users to assess the results as a whole concerning the underlying GEM. The visualizations guide the user to affected reactions, metabolites, and network areas by highlighting relevant changes between two conditions. These flux changes can then be analyzed in detail by visualizing the reaction flux distributions. We show FluxomicsExplorer's utility using a case study of the red blood cell metabolism in different blood plasma environments. Graphical abstract: Highlights: A visual analysis pipeline for Flux Sampling simulations of metabolic processes. A web-based visualization application supporting exploratory, comparative analysis. Data- and task-driven design of the application to ensure utility. A case study using real-world data to evaluate the design.